2018
DOI: 10.1186/s12870-018-1336-z
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome characterization of moso bamboo (Phyllostachys edulis) seedlings in response to exogenous gibberellin applications

Abstract: BackgroundMoso bamboo (Phyllostachys edulis) is a well-known bamboo species of high economic value in the textile industry due to its rapid growth. Phytohormones, which are master regulators of growth and development, serve as important endogenous signals. However, the mechanisms through which phytohormones regulate growth in moso bamboo remain unknown to date.ResultsHere, we reported that exogenous gibberellins (GA) applications resulted in a significantly increased internode length and lignin condensation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
61
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 94 publications
9
61
0
Order By: Relevance
“…5b), we rationally hypothesized that the PeGATA genes are also tightly regulated by phytohormones. To test our hypothesis, we performed gene expression analysis of the PeGATA genes under GA and auxin treatment based on the RNA-seq data published in the previous studies [28, 40]. A total of 12 PeGATA genes showed significant gene expression under GA treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5b), we rationally hypothesized that the PeGATA genes are also tightly regulated by phytohormones. To test our hypothesis, we performed gene expression analysis of the PeGATA genes under GA and auxin treatment based on the RNA-seq data published in the previous studies [28, 40]. A total of 12 PeGATA genes showed significant gene expression under GA treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that several gene families are involved in flower development and abiotic stress [3032, 41], the rapid-growth associated transcription factors remain elusive. The genome sequences of moso bamboo[33] and transcriptome studies [2, 27, 28, 40] provide important platforms for the identification of rapid-growth shoot and rhizome development associated gene families. The rapid-growth related genes could provide useful information for genetic manipulation of plant height in future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first plant GATA factor was identified from Nicotiana tabacum [14]. GATA factors have been identified in many plant species, including Arabidopsis (29), rice (28), apple (35), and soybean (64) [9,10,15]. Plant GATA factors are involved in many developmental processes, affecting plant architecture [16], flower development [17], hypocotyl elongation [18], and seed germination [19].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, large-scale transcriptome analysis has shown that light and phytohormones may play important roles in the rapid-growth of bamboo [27][28][29]. In addition, a large number of transcription factor families, involved in the abiotic stress response and flower development, have been studied in moso bamboo [30][31][32].…”
Section: Introductionmentioning
confidence: 99%